Are We Improving? Update and Critical Appraisal of the Reporting of Decision Process and Quality Measures in Trials Evaluating Patient Decision Aids. (October 2021) - Trenaman, Logan; Jansen, Jesse; Blumenthal-Barby, Jennifer; Körner, Mirjam; Lally, Joanne; Matlock, Daniel; Perestelo-Perez, Lilisbeth; Ropka, Mary; Stirling, Christine; Valentine, Kathrene; Vo, Ha; Wills, Celia E.; et al.
Background: In 2014, a systematic review found large gaps in the quality of reporting of measures used in 86 published trials evaluating the effectiveness of patient decision aids (PtDAs). The purpose of this study was to update that review. Methods: We examined measures of decision making used in 49 randomized controlled trials included in the 2014 and 2017 Cochrane Collaboration systematic review of PtDAs. Data on development of the measures, reliability, validity, responsiveness, precision, interpretability, feasibility, and acceptability were independently abstracted by 2 paired reviewers. Results: Information from 273 measures was abstracted, and 109 of these covered the core domains of decision processes ( n = 55) and decision quality including informed choice/knowledge ( n = 48) and values-choice concordance ( n = 12). Very few studies reported data on the performance and clinical sensibility of measures, with reliability (23%) and validity (6%) being the most common. Studies using new measures were less likely to include information about their psychometric performance compared with previously published measures. Limitations: The review was limited to reporting of measures in studies included in the Cochrane review and did not consult prior publications. Conclusion: There continues to be very little reported about the development or performance of measures used to evaluate the effectiveness of PtDAs in published trials. Minimum reporting standards have been published, and efforts to require investigators to use them are needed.